Study the effect of obesity on the level of adiponectin and DNA damage in obese patients with type2 diabetes in Wasit Province - Shamran Al-Deresawi, Tayseer (Al-Qadisiyah Journal of Pure Science, 2018)
The study present was conducted on 36 patients of both sexes with diabetes type 2 (DM2) obese aged (30-62) years. The body mass index (BMI) of those patients was â‰¥ 30 kg/m and compared to 2 groups: the first included 20 people who are non-diabetic non-obese of age (30-75) years and the second included 26 people who are non-diabetic obese with ages (22-67) years. The level of adiponectin in patients and both control groups was measured. The results showed a significant decrease in adiponectin when compared to DM2 obese and non-diabetic non-obese, while non-significant decrease were found when compared to non-diabetic type 2 obese. The results of the percentage of DNA damage of lymphocytes in patients when using comet assay test have been found to be significance (P< 0.05) in DM2 obese using Tail Mean Moment and Tail Length (Px) parameters when compared to both control groups. Also the results showed high significance (P< 0.05) in other parameters such as Olive Moment, DNA in Head (%) and DNA in Tail (%) in type2 diabetic obese group as compared to non-diabetic non-obese group.